Comparing Dynamic Pies: A Strategy for Modeling Compositional Variables in Time and Space. Issue 3 (27th November 2017) - Lipsmeyer, Christine S.; Philips, Andrew Q.; Rutherford, Amanda; Whitten, Guy D.
Abstract : Across a broad range of fields in political science, there are many theoretically interesting dependent variables that can be characterized as compositions. We build on recent work that has developed strategies for modeling variation in such variables over time by extending them to models of time series cross-sectional data. We discuss how researchers can incorporate the influence of contextual variables and spatial relationships into such models. To demonstrate the utility of our proposed strategies, we present a methodological illustration using an analysis of budgetary expenditures in the US states.